Detection and Attribution of a Spatial Heterogeneity in the Temporal Evolution of Bulgarian River Discharge - Natalya A. Kilifarska; Gergana I. Metodieva; Antonia Ch. Mokreva (Geosciences)
The hydrosphere is an element of the climate system and changes in the latter are reasonably projected over the river outflow. Climatic changes, however, are unevenly distributed over the Earth, and understanding their regional imprint on the hydrosphere is of great importance. In this study, we have conducted a statistical analysis of the monthly maximum and minimum river discharge recorded in 22 hydrological stations located on 19 of the Bulgarian rivers during the period 1993–2022. We have found that in half of the river basins, the trend of the spring maximum discharge is significantly positive (α = 0.05). In the other half of the stations, the trend is neutral. The stations with a positive trend are not randomly distributed but grouped, forming a pattern crossing the country from northwest to southeast. This pattern of trend distribution raises questions about the causes of the irregular hydrological response to the rising global near-surface temperatures. A comparison of hydrological data with some climatic variables (i.e., temperature, precipitation, and ozone at 70 hPa), combined with neural network analysis results, suggests ozone as a possible reason for the heterogeneous hydrological response. Its effect could be explained by an imposed episodic warming of the near-surface temperature due to fluctuations in the ozone density near the tropopause, which in turn favours the faster melting of ice and snow in the corresponding river basins.